Penghentian Penuntutan Tindak Pidana Ringan melalui Penerapan Restorative Justice Dihubungkan dengan Tujuan Pemidanaan - Namira Gupita Rakasiwi Aria; Chepi Ali Firman Zakaria (UNISBA Press, 2023)
Abstract. Prison sanctions are excellent for law enforcement officials and problems in law enforcement in West Java, as a result of which the state budget swells for prisoners and the overcapacity of prison residents in the West Java region is a problem that needs to be addressed, this is in order to reconstruct new thinking in order to realize the goal of a more humanist punishment. The author examines the termination of prosecution of minor crimes through the application of restorative justice linked to the purpose of punishment with the aim of knowing and analyzing considerations for the application of restorative justice in minor crimes based on criminal law and to find out and analyze the juridical implications of restorative justice in Attorney General Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice in the West Java High Prosecutor's Office. To achieve the above objectives, the author conducts descriptive research, which is to analyze and describe systematically, factually, and accurately the provisions related to Juridical implications regarding the termination of prosecution of minor criminal acts through the application of restorative justice. The type of research used is normative juridical using a statute approach. Data are obtained through the study of documents and analyzed using qualitative normative methods. Based on the results of the study, it is known that the consideration of stopping the prosecution of minor criminal cases in the West Java High Prosecutor's Office is a legal breakthrough in an effort to resolve criminal cases effectively based on the principles of balance, sense of justice, the principle of benefits and creating social welfare, The public prosecutor has the authority to stop prosecutions for the benefit of the victim and other protected legal interests in order to avoid negative stigma, avoidance of reprisals, response and harmony of society, and decency and public order by taking into account the principle of salus populi suprema lex which is meaningful